EFFICIENCY OF FUNDS ALLOCATED TO ENSURE EMPLOYMENT (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article will analyze the issues of improving the efficiency of the funds allocated for the employment of the population and their economic significance. Currently, the country is undergoing a wide range of reforms aimed at increasing population employment, reducing unemployment and expanding citizens ' sources of income. In particular, special attention is paid to ensuring the stability of the labor market by creating new jobs, vocational training, and developing small businesses and private entrepreneurship. At the same time, the effective and targeted allocation of financial resources by the state is one of the main factors determining the effectiveness of these processes. The article examines in depth the mechanisms for financing programs aimed at ensuring employment, the distribution of funds across sectors and regions, and their practical results. The criteria used to assess the effectiveness of allocated funds, as well as the status of monitoring and control systems, will also be analyzed.